Carbonizable calcium silicates by CO2 atmosphere in a pressure chamber - Andrea Jančíková; Michal Křištof; Karel Dvořák (Acta Polytechnica CTU Proceedings)
The paper deals with the possibility of different calcium silicate minerals namely wollastonite (CS), belite (C2S), and rankinite (C3S2) on their curing in CO2 atmosphere. It describes the laboratory preparation of these individual minerals from p.a. pure chemical clean materials. For comparison a representative sample of natural mined wollastonite was chosen for carbonation as well. Following this, for setting basic parameters analyses determining the properties of the samples by XRD analysis and Rietveld evaluation, particle size characterization by laser granulometry and milling fineness by the Blaine method. It also addresses the issue of forming samples suitable for carbonation using a hydraulic press and the actual curing and conditions necessary for carbonation of the minerals in pressure chamber. It summarizes the measured results of compressive strengths, weight changes and mineralogical evaluation of the composition of the samples before and after carbonation. In the conclusion, together with a summary of the measured findings, it is pointed out what direction further research in this field should be aimed for.